Cloud security - Hein Htet, Zaw (2014)
Cloud computing is becoming popular due to its convenience and no initial capital cost to buy the physical resources. Users can conveniently use resources in the cloud such as computing resources or storage resources, in a minimum setup time. Moreover, they only need to pay for only what they use, which is analogous to using electricity. However, the security concerns for the data is high as the cloud technology is relatively new and security holes exist in this new technology.